ANTIOXIDANT AND FREE RADICAL SCAVENGING POTENTIAL OF ETHANOLIC FRACTION OF ADHATODA VASICA IN A549 CELL LINE - PANT, MAMTA; BASU, SUJATA; K SINDHU, RAKESH; ., RACHANA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: To characterize and standardize the ethanolic extract of Adhatoda vasica (AV) and evaluate its antioxidant potential in vitro, and to study its free radical scavenging effect in A549 cell line. Methods: Antioxidant activity of AVE through DPPH, ABTS, superoxide radical scavenging activity, H2O2, NO and Lipid peroxidation assays were carried out. Results: In A549 cell line, the NO scavenging ability of AVE was analysed through NO production measurement. IC values of ethanolic extract through DPPH, ABTS, superoxide radical scavenging activity, H 2 O 2 50 , NO and lipid peroxidation assays were found to be 64, 200, 54, 62, 40 and 340 Âµg/ml, respectively. The reducing power was found to increase in a concentration dependent manner. AVE (1 - 2Âµg/ml) scavenged NO radicals (11% and 28% in comparison to control). Conclusion: The present study showed the ethanolic extract of AV to be a good oxygen radical scavenger and a natural source of antioxidants. AVE showed significant nitric oxide radical scavenging activity in A549 cell line. Keywords: Adhatoda vasica, Phytochemicals, Flavonoids, Tannins, Antioxidant potential.